Two years of oceanic observations below the Fimbul Ice Shelf, Antarctica - Hattermann, Tore; Nøst, Ole Anders; Lilly, Jonathan M; Smedsrud, Lars H (Geophysical Research Letters, 2012)
The mechanisms by which heat is delivered to Antarctic ice shelves are a major source of uncertainty when assessing the response of the Antarctic ice sheet to climate change. Direct observations of the ice shelf-ocean interaction are extremely scarce and in many regions melt rates from ice shelf-ocean models are not constrained by measurements. Our two years of data (2010 and 2011) from three oceanic moorings below the Fimbul Ice Shelf in the Eastern Weddell Sea show cold cavity waters, with average temperatures of less than 0.1°C above the surface freezing point. This suggests low basal melt rates, consistent with remote sensing-based, steady-state mass balance estimates for this sector of the Antarctic coast. Oceanic heat for basal melting is found to be supplied by two sources of warm water entering below the ice: (i) eddy-like bursts of Modified Warm Deep Water that access the cavity at depth for eight months of the record; and (ii) fresh surface water that flushes parts of the ice base with temperatures above freezing during late summer and fall. This interplay of processes implies that basal melting at the Fimbul Ice Shelf cannot simply be parameterized by coastal deep ocean temperatures, but instead appears directly linked to both solar forcing at the surface as well as to the dynamics of the coastal current system.
Keywords: Sørishavet; Weddellhavet; fysisk oseanografi; innlandsis; isbrem; isshelf; klimaendringer; smelting

Wind-driven spreading of fresh surface water beneath ice shelves in the Eastern Weddell Sea - Zhou, Qiming; Hattermann, Tore; Nøst, Ole Anders; Biuw, Martin; Kovacs, Kit M; Lydersen, Christian (Journal of Geophysical Research: Oceans, 2014)
Abstract Solar heated, fresh Antarctic Surface Water (ASW) is a permanent feature along the Eastern Weddell Sea (EWS) coast in summer down to a depth of roughly 200 m. Recently, ASW has been observed beneath the Fimbul Ice Shelf, suggesting that it might play an important role in basal melting. We propose that wind-driven coastal downwelling is the main mechanism that spreads ASW beneath the ice shelf in this sector of Antarctica. We validate this hypothesis with observations, scaling analyses, and numerical modeling, along three principle lines: (i) data analyses of about 1500 salinity profiles collected by instrumented seals indicate that the observed freshening of the coastal water column is likely explained by the on-shore Ekman transport and subsequent downwelling of ASW; (ii) an analytical model of the coastal momentum balance indicates that wind-driven downwelling is capable of depressing the buoyant surface water to a depth similar to the ice shelf draft; and (iii) simulations from both idealized and regional eddy-resolving numerical ice shelf/ocean models support our proposition. Our main conclusion is that wind-driven spreading of ASW beneath the ice shelf occurs when downwelling exceeds the depth of the ice shelf base. Furthermore, our study adds to the understanding of the oceanic processes at the Antarctic Slope Front in the EWS, with possible implications for other sectors of Antarctica.
Keywords: Sørishavet; Weddellhavet; isbrem; isshelf; oseanografi; overflatevann; smelting; vannmasser; vannvirvler

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Eddy overturning of the Antarctic Slope Front controls glacial melting in the Eastern Weddell Sea - Nøst, Ole Anders; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Zhou, Qianhe; Smedsrud, Lars Henrik; Kovacs, Kit M (Journal of Geophysical Research: Oceans, 2011)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; oseanografi